Transformative reparations for women and girls at the extraordinary chambers in the courts of Cambodia - Williams, Sarah (International journal of transitional justice, 2016)
Reparations programmes are one form of response to violence. However, scholars have criticized their tendency to focus on restoring victims to the position they were in before the conflict began, usually through awarding restitution, compensation or rehabilitation measures. Instead, critics have suggested that reparations should aim to transform the societal conditions that contribute to sexual violence and the inequality of women and girls through recognition, redistribution and representation. This article builds upon this emerging scholarship to explore the potential for transformative reparations in international criminal tribunals through examining the reparations mandate and practice of the Extraordinary Chambers in the Courts of Cambodia (ECCC). It concludes that the ECCC’s legal and institutional framework, and the context in which it operates, limit the contribution that it can make to transformation. It is therefore important to be realistic about what can be expected from such institutions.